General characteristics of dental morbidity in children against orthodontic treatment - Kovach I.V.; Lavrenyuk Y.V. (Medičnì Perspektivi)
A wide spread of orthodontic treatment showed a fairly high risk of complications developed from the use of various devices. The aim of our study was to determine the general characteristics of dental morbidity in children with orthodontic treatment. According to the survey the most common pathologies in children with orthodontic problems are dental caries (87,8-92,9%) and chronic catarrhal gingivitis (81.2-84.1%). The prevalence of different types of diseases of the mucous membrane and soft tissues of the oral cavity in children surveyed was 30.5-32.9%. Non-caries lesions of dental hard tissues occurred in 39.5-40.9% of the children surveyed, local enamel hypoplasia was observed in 42.9%, systemic enamel hypoplasia made up 17.8%, signs of hypersensitivity of enamel were found in 9.6%, and the wedge defects – in two children.